Prevalence and pathologic study of eimeria cameli in slaughtered camels - Reza Kheirandish; Saeid R. Nourollahi-Fard; Zahra Faryabi (Eurasian Journal of Veterinary Sciences)
Aim: This study was carried out to determine Eimeria infection in slaughtered camel and describe the gross and histopathologic lesions caused by Eimeria species in the intestinal tract. Materials and Methods: Slaughtered 100 camels (68 males, 32 females, 6 months to 8 years, Kerman) were investigated for the presence of Eimeria parasites microscopically in intestinal tracts. Camels were classified into 3 groups according to the age (<2 years, 2-4 years, >4 years) and sex (male, female). The prevalence of Eimeria spp. infection and the intensity of faecal oocysts were determined using floatation and sporulation techniques. Tissue samples were taken from the intestinal tracts and then fixed in 10% buffered formalin. They were processed and embedded in paraffin. Sections of 5 μm thickness were cut and stained with Hematoxylin and Eosin. Results: Eimeria cameli were found in 29 (29%) of the 100 camels. Sex and age of camels did not have significant (p>0.05) effect on prevalence. Microscopic examination revealed eosinophilic enteritis and existence of developmental stages of the parasite such as giant schizonts, microgamont, macrogametocytes, and oocysts in the lacteals of lamina propria and in the epithelium of Lieberkuhn glands. Conclusion: Eimeria cameli infection is prevalent in camels in the south-eastern part of Iran and the evaluation of infection potential can be useful when considering control programs.